COMPUTERIZED PAYMENT SYSTEMS STUDENT AT THE YOUTH DANCE STUDIO DANCE-MUSIC-THEATER BETAWI - Muhammad Indra Jaya; Hariyanto, Skom, MMSI Hariyanto, Skom, MMSI (Jurnal Sistem Informasi, 2000)
Based on research from the current system is still manual, which produced reportssometimes late, this was due to the complexity of data processing that is causingerrors and repetitive work in producing the report and the problems that hamperstudent payment data processing. Therefore, the authors make a new system to ensureaccuracy and security and can be more effective for data processing students'payments at the time will come in this era of computerization. Can also be useful insupporting the decision for the leadership.